ANALISIS PERBANDINGAN KINERJA PEGAWAI DI KANTOR CAMAT KABUPATEN ROKAN HULU (STUDI KASUS KANTOR CAMAT TAMBUSAI DAN KANTOR CAMAT RAMBAH) - Andi Afrizal., Fauziah, Makmur, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2017)
This study aims to determine the Employee Performance Comparison In Rokan Hulu District Office (case study Tambusai sub-district office and the district office Rambah). using saturated sampling technique then obtained a total sample of 51, that all employees who work at the office Head office Head Tambusai and employees Rambah. This study uses quantitative methods and use data collected with observation, interviews and questionnaires. After doing the research results of employee performance comparison Tambusai sub-district office and the district office employees Rambah is Good in serving their communities. It can be seen from the data processing an average yield of TCR at the district office Tambusai of 78.3 with Good ratings category, and the average yield of the TCR to the district office Rambah amounted to 79.8 which is the category Good. Recommended on all employees Tambusai sub-district office and the district office employees Rambah to always maintain and improve its performance in providing good service to the community.